Prevalence and characterization of antimicrobial-resistant Escherichia coli in chicken meat from wet markets in Hong Kong - Hasib, F. M. Yasir; Magouras, Ioannis; St-Hilaire, Sophie; Paudel, Surya; Kamali, Maedeh; Lugsomya, Kittitat; Lam, Hoi Kiu; Elsohaby, Ibrahim; Butaye, Patrick; Nekouei, Omid (Frontiers in Veterinary Science, 2024)
Given the close contact between animals, animal products, and consumers in wet markets, fresh meat products are considered a potential source and disseminator of antimicrobial-resistant (AMR) bacteria near the end of the food chain. This cross-sectional study was conducted to estimate the prevalence of select AMR-E. coli in fresh chicken meat collected from wet markets in Hong Kong and to determine target genes associated with the observed resistance phenotypes. Following a stratified random sampling design, 180 fresh half-chickens were purchased from 29 wet markets across Hong Kong in 2022 and immediately processed. After incubation, selective isolation was performed for extended-spectrum β-lactamase producing (ESBL), carbapenem-resistant (CRE), and colistin-resistant (CSR) E. coli. The bacterial isolates were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Disc Diffusion was used to determine the susceptibility of ESBL-and CRE-E. coli isolates. The broth microdilution method was used to determine the minimum inhibitory concentration of CSR-E. coli. Targeted resistance genes were then detected by PCR.The prevalence of ESBL-E. coli and CSR-E. coli were estimated at 88.8% (95% CI: 83.4-93.1%) and 6.7% (95% CI: 3.5-11.4%), respectively. No CRE-E. coli isolate was detected.The blaCTX-M-1 gene was the most common β-lactamase group in isolated E. coli (80%), followed by blaTEM (63.7%); no blaSHV gene was detected. Forty-five percent of the isolates had blaTEM and blaCTX-M-1 simultaneously. The mcr-1 gene was detected in all 12 CSR isolates. Of 180 meat samples, 59 were from Mainland China, and 121 were locally sourced. There was no statistically significant difference in the prevalence of ESBL-and CSR-E. coli between the two sources. Our findings can be used to inform food safety risk assessments and set the stage for adopting targeted control and mitigation measures tailored to the local wet markets.